Cue-reliance and vowel perceptual patterns of Cypriot Greek children who learn English - Georgios P. Georgiou (Estudios de Fonética Experimental, 2019)
The aim of the present study is to investigate the vowel perceptual patterns of Cypriot Greek children who learn English as a foreign language in Cyprus and their cue-reliance during L2 vowel categorization. To this purpose, 26 native speakers of Cypriot Greek participated in a perceptual assimilation task and an AXB discrimination task. The findings showed that learners assimilated two or more English vowels to a single phonological category of their native language. Furthermore, their discrimination over selected English vowel contrasts ranged from poor to moderate. The small L1 vowel inventory of learners resulted in multiple assimilations of L2 vowels to the same L1 phonological category and the lack of linguistic experience prevented the establishment of novel phonological categories. Also, the temporal cues of L2 vowels were not employed for their better fitting on the already assimilated L1 phonological categories. The predictions were in general consistent with the assumptions of the Perceptual Assimilation Model-L2.